The impact of resection margin on overall survival for patients with colon cancer liver metastasis varied according to the primary cancer location. Issue 6 (June 2019) - McVey, John C.; Sasaki, Kazunari; Margonis, Georgios A.; Nowacki, Amy S.; Firl, Daniel J.; He, Jin; Berber, Eren; Wolfgang, Christopher; Miller, Charles C.; Weiss, Matthew; Aucejo, Federico N.
Abstract : Introduction: Investigation into right and left-sided primary colon liver metastasis (CLM) has revealed differences in the tumor biology and prognosis. This indicates that preoperative and operative factors may affect outcomes of right-sided primary CLM differently than left. This retrospective analysis investigated the effects of resection margin stratified by left and right-sided primary CLM on overall survival (OS) for patients undergoing hepatectomy. Methods: A total of 732 patients undergoing hepatic resection for CLM at the Cleveland Clinic and Johns Hopkins were identified between 2002 and 2016. Clinically significant variables were analyzed using Cox proportional hazard regression. The cohort was then divided into patients with right and left-sided CLM and analyzed separately using Kaplan Meier analysis and Cox proportional hazard regression. Results: Cox proportional hazard regression showed that left-sided CLM with an R0 margin was a statistically significant predictor of OS even after controlling for other important factors (HR = 0.629, P = 0.024) but right-sided CLM with R0 margin was not (HR = 0.788, P = 0.245). Kaplan–Meier analysis demonstrated that patients with a left-sided CLM and R0 margin had the best prognosis (P = 0.037). Conclusion: Surgical margin is an important prognostic factor for left-sided primary CLM but tumor biology may override surgical technique for right-sided CLM. Abstract : Abstract